Policies, institutions and markets: The first eighteen months - CGIAR Research Program on Policies, Institutions and Markets (International Food Policy Research Institute, 2013)
This report highlights some of the most notable achievements and new directions it has achieved. For example, the foresight modeling team is breaking new ground in quantitative thinking about our agricultural future, the value chains teams are identifying new approaches to linking smallholders to markets, and PIM’s gender researchers are developing sex-disaggregated data that will open new terrain in gender research.